Evaluation of chlorophyll content and membrane stability under oxidative stress induced by glyphosate herbicide as indicators of drought tolerance in some advanced durum wheat (Triticum durum L.) lines: in vitro study - Benkadja, Sarah; Oulmi, Abdelmalek; Frih, Benalia; Bendada, Hocine; Guendouz, Ali; Benmahammed, Amar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Oxidative stress caused by glyphosate is a complex chemical and physiological phenomenon and develops as a result of overproduction and accumulation of reactive oxygen species (ROS). This study was carried out in vitro at the National Institute of Agronomic Research of Algeria (INRAA) Setif, to select the most susceptible durum wheat (Triticum durum L.) under oxidative stress induced by glyphosate herbicide by evaluating chlorophyll content degradation and cell membrane leakage. Genotypes showed significant variations in almost all the studied traits. The chlorophyll loss ratio ranged from 26.42 % for the genotype G5 to 48.75 % for the local variety Boutaleb, glyphosate sensitivity index values were found to be between 0.65-1.2, the advanced line G5 was found to be the most tolerant under oxidative stress with the lowest chlorophyll loss ratio and lowest Glyphosate sensitivity index. Furthermore, the advanced line G4 recorded the highest electrolyte leakage (80.16 %) while G6 showed the lowest estimate (50.77 %). Therefore, advanced lines G5 and G6 appear the most suitable for the growing conditions.